A Compact Novel Quad Patch High Gain Triple Band Microstrip Antenna for 5G/6G mm Wave Applications - Singh, R. K.; Mamta, K. (Journal of Scientific Research, 2024)
This paper presents a compact, novel, quad patch and triple band single substrate microstrip patch antenna for 5G/6G mm wave applications. The aim is to design an antenna within the K-band with three resonance frequencies at 24, 29, and 34 GHz. The antenna is designed on a volumetric dimension of 11×12.7×1.6 mm3. The substrate used is FR4 (dielectric constant 4.4), having a loss tangent of 0.0022. A microstrip line of width 1 mm for a 50 Ω impedance line is used to match with the load antenna, which has four rectangular connected patches. Patch dimensions come from standard antenna equations and simulation done on Ansys High-Frequency Structure Simulator software. Validation of simulated results is done through measurements on the prototype antenna. A substantial good agreement is found between the simulated and measured results. The gain of the proposed antenna is 6.16 dBi, with return loss being ≤-10 dB. Bandwidths are 1.1 GHz (23.8 - 24.9 GHz), 0.9 GHz (28.6 - 29.5 GHz), and 0.8 GHz (33.7 – 34.5 GHz), respectively. The far-field radiation characteristics of both E-plane and H-plane are also reported. The proposed design is suitable for mm wave applications, including smart vehicles, global positioning systems, radio frequency identifications, etc.